The influence of Social media marketing on consumer purchase intention: investigating the effect of non-local brands. (Institute of Business Management, 2022)
A large number of people are using social media which gives advantages to marketers to keep connected with their customers and also keep updated about what customers want. In this research, we are discussing the effect of social media marketing from the perception of non-local brands. The problem that we identified in the previous research is the easy usage of non-local brands' websites and apps which could be a concern for the social media consumers' purchase intentions in Pakistan which are being investigated in this research along with other variables. The literature of the study includes a detailed discussion about the hypothesis which consists of the relationship between brand trust, brand community, brand awareness, emotional attachment, Interaction and ease of use with purchase intention, and the relationship between purchase intention and brand loyalty. This research approach was quantitative. The Data were collected online from 351 social media users in Pakistan. The research model was empirically tested using a structural equation model. This research has seven hypotheses in which H1, H2, H3 are rejected and H4 to H7 are accepted. This research has identified that companies should increase interaction, emotional attachment, and ease of use through social media to influence the consumer's purchase intention to increase brand loyalty.